PROBLEMATIKA PEREMPUAN SINGLE PARENT DALAM MEMBENTUK MORALITAS ANAK DI DESA BANARAN KABUPATEN NGANJUK - Utari, Wahyu Puji Suli; Jatiningsih , Oksiana (Universitas Negeri Surabaya (Unesa), 2024)
The important role of both parents in forming a child's character in growth, because parents are role models for children. Forming children's morality is certainly not easy for single parent women who have different problems compared to family problems in general, because in single parent women's families the father figure who serves as the leader figure for the family must be replaced by the single parent woman herself. This research aims to describe the problems and strategies of single-parent women in shaping children's morality in Banaran Village. The approach in this research uses a qualitative approach. The subjects of this research were single parent women who had teenage children. The selection of research subjects was carried out using purposive sampling technique. The data collection technique uses in-depth interviews. The collected data was analyzed using the Miles and Huberman model which has four stages, namely data reduction, data presentation, and drawing conclusions using Brofenbrenner's ecological theory. The results of this research show that there are problems faced, namely 1.) Lack of opportunities to meet children, 2.) Rumors about unfavorable news in the community towards informants, 3) Children's resistance to parental advice. Then there are several strategies, namely 1.) Supervising children's behavior through relatives and neighbors, 2.) providing understanding to children, 3.) Choosing a good school environment for children, 4.) Implementing time limits in accessing media and technology as a form of supervision and control of children.